Management of Flabby Maxillary Anterior Ridge: A Case Report - Gurung, SM; Pathak, B; Devkota, D (Journal of Nepalese Prosthodontic Society, 2023)
A flabby ridge occurs by replacing bone with connective fibrous tissues and is most commonly found in the anterior maxillary ridge. Flabby tissues present a challenging clinical scenario for the clinician. Making an accurate impression of these tissues is crucial for producing a prosthesis that fits well. In this case report, an open tray approach is used on a patient who has completely edentulous maxillary arch with flabby tissue in anterior region.